2020
DOI: 10.1097/jte.0000000000000162
|View full text |Cite
|
Sign up to set email alerts
|

The Toll of Student Debt: Stress Among Health Professions Students and the Promising Role of Financial Self-Efficacy on Career Choices

Abstract: Introduction. As the cost of higher education rises, the debt associated with degree attainment also increases, including that of the Doctor of Physical Therapy degree. Research suggests that a relationship between financial debt and postprofessional career aspirations may exist, and financial self-efficacy could attenuate debt-related stress. These relationships have not been studied in the health professions outside of medicine. Methods. A total of 13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 22 publications
2
6
0
Order By: Relevance
“…15 Indeed, research has shown an association between financial self-efficacy and lower ratings of stress from student loan debt among graduate students in health-care fields. 8 Conversely, recent research has also shown that although financial literacy can increase one's knowledge of finance, it does little to change financial behaviors. 16 Additional research is warranted that looks specifically at improving our understanding of financial behavior to better influence financial outcomes and decisions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Indeed, research has shown an association between financial self-efficacy and lower ratings of stress from student loan debt among graduate students in health-care fields. 8 Conversely, recent research has also shown that although financial literacy can increase one's knowledge of finance, it does little to change financial behaviors. 16 Additional research is warranted that looks specifically at improving our understanding of financial behavior to better influence financial outcomes and decisions.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5] Research in human medicine has shown how educational debt among medical students and residents can influence mental health and well-being, academic performance, career choices, lifestyle conditions, and other variables. [6][7][8][9] To the authors' knowledge, similar…”
mentioning
confidence: 82%
“…In order to explain the pervasiveness of research on ECRs, other scholars have studied professional identity (Karaharju-Suvanto et al, 2021), stress and financial selfefficacy (Dickson et al, 2020), work-life balance (Gutman, 2020;Krilid et al, 2018) career trajectory (Belfi, 2021;Emmanouil et al, 2017), lived experiences (Caretta, 2018;Whipp & Geronime, 2017), doctoral teaching development (Connolly et al, 2018), school loans/educational debt (Rothstein & Rouse, 2011;Zhang, 2013), career progression (Goldacre et al, 2010), and the pathway choices (Carrico et al, 2012) of ECRs. However, some studies with a focus on early-career researchers have considered several aspects of mentorship such as information mentorship (Al Shebli et al, 2020), mentorship experiences (Kay et al, 2009;Lalani et al, 2018;Mgaiwa & Kapinga, 2021), workplace resources (Perumalswami et al, 2020), effective mentorship (Diggs-Andrews et al, 2021), online mentorship (Bielczyk et al, 2019), supporting early-career mentorship (Kwamie & Jalaghonia, 2020), research mentorship (Hernandez-Lee & Pieroway, 2018Van Schalkwyk et al, 2017), induction and mentorship programs (Weldon, 2018), and also peer mentoring programs (Brody et al, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Student loan burden can contribute to increased stress levels and significantly impact healthcare career aspirations among those considering a healthcare profession. 11 12 Understanding the funding mechanisms behind higher education can be beneficial for not only professionals currently experiencing student loan repayments but also for recruitment efforts to grow the profession.…”
Section: Why Lobby At the State Level?mentioning
confidence: 99%